Prosody of F. W. Haack’s dictionary - Rinkevičius, Vytautas (Vilnius University Open Series, 2022)
The article deals with the notation of prosodic features of Lithuanian words in F. W. Haack’s Lithuanian-German and German-Lithuanian dictionary (1730). First, the place of stress (in some cases also tone) is shown by Haack’s diacritical marks. Second, in some cases the place of stress is indirectly reflected by orthographic devices used to mark vowel quantity, e.g., the use of two different letters and <y> for the long vowel y or the use of double consonants to mark the brevity of the preceding vowel. Finally, a separate valuable source of data for Lithuanian historical accentology is constituted by hand-written diacritical marks placed above some words in the copy of the dictionary held at Vilnius University Library.